2012
DOI: 10.4081/ijas.2012.e56
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytase with or without multienzyme supplementation on performance and nutrient digestibility of young broiler chicks fed mash or crumble diets

Abstract: A total of 210 unsexed 1-day old Arbor Acres broiler chicks were wing banded and randomly distributed among 30 cages of 7 birds per cage keeping equal initial BW during days 1-20 of age. A factorial design (2×3) was used in which there were two feed forms (mash vs crumble diet) and three enzyme treatments (unsupplemented, phytase, phytase plus multienzyme). Each treatment was replicated 5 times with 7 chicks per replicate. Body weight (BW), body weight gain (BWG) and feed conversion ratio (FCR) of fed chicks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 31 publications
11
72
1
1
Order By: Relevance
“…Regarding inclusion of wheat bran, result of current study are in agreement with the results of Mathlouthi, Larbier, Mohamed, and Lessire (2002), but application of enzyme showed inconsistency owing to the difference in enzyme used, nutrient concentration, type of diet and birds age. The application of phytase in this study did not improved performance which disagreed with previous reports (Tangendjaja et al, 2002;Selle & Ravindran, 2007;Liu et al, 2008b;Attia et al, 2012). Liu, Ru, Cowieson, Li, and Cheng (2008b) reported that supplementation with phytase improve feed intake, body weight, and gain to feed intake ratio of broilers.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Regarding inclusion of wheat bran, result of current study are in agreement with the results of Mathlouthi, Larbier, Mohamed, and Lessire (2002), but application of enzyme showed inconsistency owing to the difference in enzyme used, nutrient concentration, type of diet and birds age. The application of phytase in this study did not improved performance which disagreed with previous reports (Tangendjaja et al, 2002;Selle & Ravindran, 2007;Liu et al, 2008b;Attia et al, 2012). Liu, Ru, Cowieson, Li, and Cheng (2008b) reported that supplementation with phytase improve feed intake, body weight, and gain to feed intake ratio of broilers.…”
Section: Resultscontrasting
confidence: 56%
“…The effect of dietary phytate and phytase supplementation on the production performance and nutrient digestibility of poultry have received remarkable attention in the scientific studies (Liu, Ru, Li, & Cowieson, 2008a;Attia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the difference in response of broilers to dietary inclusion of CM between the current study and that of our previous research with regards to relative weights of pancreases and cecal could be due to the differences in Journal of Poultry Science,54 (4) phytate content of CM based diets and fermentable sugars content of SBM based diets, respectively. Phytase was shown to improve phytate, amino acids and energy utilization of ducks (Attia, 2003), laying Japanese quail hens (Attia et al, 2008), and broiler chickens (Attia et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate (SR, 100 -mortality rate) during 1-28 days of age was recorded. The European production efficiency index (EPEI) was calculated, as cited by Attia et al (2012).…”
Section: Methodsmentioning
confidence: 99%